Sistem Keamanan Ruangan Berbasis Internet of Things Menggunakan Single Board Computer - Rima Dias Ramadhani; Afandi Nur Aziz Thohari; Novanda Alim Setya Nugraha (Universitas Islam Sumatera Utara, 2020)
Closed Circuit Television (CCTV) is a security system to monitoring a room. In recent years, the use of CCTV is becoming less effective. CCTV usually have expensive rental fees and expensive device. Surveillance system using CCTV still need security officer to monitoring room condition through TV Screen. In this research purposed to build surveillance system using artificial intelligence method. The system features are detect object and send notification through Short Message Service (SMS). Single Board Computer (SBC) is used to processing video data. Technique for detecting objects is Structural Similarity (SSIM). Thought this technique, system have more accuration because it can't read shadow as object. Based on testing result obtained that system can detect object and send notification to user through SMS. System can't read object if low light intensity, but if high intensity of light the system can detect objects that have far position. Maximum frame rate that used to capture video is 60 fps, because limitation of SBC that used.